Clozapine-Induced Cardiovascular Side Effects and Autonomic Dysfunction: A Systematic Review - Yuen, Jessica W. Y.; Kim, David D.; Procyshyn, Ric M.; White, Randall F.; Honer, William G.; Barr, Alasdair M. (Frontiers in Neuroscience, 2018)
Background: Clozapine is the antipsychotic of choice for treatment-resistant schizophrenia and has minimal risk for extrapyramidal symptoms. Therapeutic benefits, however, are accompanied by a myriad of cardiometabolic side-effects. The specific reasons for clozapine’s high propensity to cause adverse cardiometabolic events remain unknown, but it is believed that autonomic dysfunction may play a role in many of these. Objective: This systematic review summarizes the literature on autonomic dysfunction and related cardiovascular side effects associated with clozapine treatment. Method: A search of the EMBASE, MEDLINE and EBM Cochrane databases was conducted using the search terms antipsychotic agents, antipsychotic drug*, antipsychotic*, schizophrenia, schizophren*, psychos*, psychotic*, mental ill*, mental disorder*, neuroleptic*, cardiovascular*, cardiovascular diseases, clozapine*, clozaril*, autonomic*, sympathetic*, catecholamine*, norepinephrine, noradrenaline, epinephrine, adrenaline. Results: The search yielded 37 studies that were reviewed, of which only 16 studies have used interventions to manage cardiovascular side effects. Side effects reported in the studies include myocarditis, orthostatic hypotension and tachycardia. These were attributed to sympathetic hyperactivity, decreased vagal contribution, blockade of cholinergic and adrenergic receptors, reduced heart rate variability and elevated catecholamines with clozapine use. Autonomic neuropathy was identified by monitoring blood pressure and heart rate changes in response to stimuli and by spectral analysis of heart rate variability. Metoprolol, lorazepam, atenolol, propranolol, amlodipine, vasopressin and norepinephrine infusion were used to treat tachycardia and fluctuations in blood pressure, yet results were limited to case reports. Conclusion: The results indicate there is a lack of clinical studies investigating autonomic dysfunction and a limited use of interventions to manage cardiovascular side effects associated with clozapine. As there is often no alternative treatment for refractory schizophrenia, the current review highlights the need for better designed studies, use of autonomic tests for prevention of cardiovascular disease and development of novel interventions for clozapine-induced side effects.